2018
DOI: 10.13181/mji.v27i4.3024
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness and safety analysis of dual antiplatelet therapy comparing aspirin–clopidogrel to aspirin–ticagrelor in patients with acute coronary syndrome

Abstract: Background: Dual antiplatelet therapy (DAPT) using either an aspirin–clopidogrel (A–C) combination or aspirin–ticagrelor (A–T) combination has become the standard therapy for acute coronary syndrome (ACS). Ticagrelor shows better pharmacokinetic profiles but is more expensive. This study aimed to compare cost-effectiveness and safety profiles of A–C versus A–T in patients with ACS.Methods: This was a retrospective cohort study of ACS patient at the Cipto Mangunkusumo Hospital between 2014 and 2016. ACS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Table 3 shows that the use of the combination regimen was greater (81.6%) than the monotherapy regimen (18.4%). These results are in line with the study of Nafrialdi et al, (2018) which showed that the use of a combination therapy regimen of clopidogrel and aspirin in patients with ACS was greater (68.3%) compared to ticagrelor monotherapy (31.7%).…”
Section: Resultssupporting
confidence: 90%
“…Table 3 shows that the use of the combination regimen was greater (81.6%) than the monotherapy regimen (18.4%). These results are in line with the study of Nafrialdi et al, (2018) which showed that the use of a combination therapy regimen of clopidogrel and aspirin in patients with ACS was greater (68.3%) compared to ticagrelor monotherapy (31.7%).…”
Section: Resultssupporting
confidence: 90%
“…However, the main conditions included in the MACE studies were angina pectoris, recurrent AMI, stroke, and death. The proportion of MACEs in previous studies showed different results (3,4,48) In this study, women marginally have a higher risk of developing MACEs than men. The proportion of women (7.5%) was smaller than that of men (92.5%), resulting in a higher risk of MACEs for women.…”
Section: Association Between Several Factors and Macesmentioning
confidence: 52%
“…However, the main conditions included in the MACE studies were angina pectoris, recurrent AMI, stroke, and death. The proportion of MACEs in previous studies showed different results ( 3 , 4 , 48 ). Nafrialdi et al ( 3 ) found a proportion of 29.3% in post-PCI patients in the 3 months of observation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations